2020
DOI: 10.1038/s41598-020-60905-7
|View full text |Cite
|
Sign up to set email alerts
|

BCAP31, a cancer/testis antigen-like protein, can act as a probe for non-small-cell lung cancer metastasis

Abstract: Non-small-cell lung cancer (NSCLC) represents most of lung cancers, is often diagnosed at an advanced metastatic stage. Therefore, exploring the mechanisms underlying metastasis is key to understanding the development of NSCLC. The expression of B cell receptor-associated protein 31 (BCAP31), calreticulin, glucose-regulated protein 78, and glucose-regulated protein 94 were analyzed using immunohistochemical staining of 360 NSCLC patients. It resulted that the high-level expression of the four proteins, but par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
(39 reference statements)
1
14
0
Order By: Relevance
“…Further GSEA analysis showed that BCAP31 may participate in multiple biological processes, such as protein transport, metabolism and organelle organization. We have found in previous studies that BCAP31 may regulate the migration and invasion ability of cancer cells by regulating the expression of cytoskeletal proteins, such as Drebrin, M-RIP, SPECC1, Nexilin, and F-actin (Dang et al, 2018;Wang et al, 2020). These results are consistent with our GSEA analysis results.…”
Section: Discussionsupporting
confidence: 93%
“…Further GSEA analysis showed that BCAP31 may participate in multiple biological processes, such as protein transport, metabolism and organelle organization. We have found in previous studies that BCAP31 may regulate the migration and invasion ability of cancer cells by regulating the expression of cytoskeletal proteins, such as Drebrin, M-RIP, SPECC1, Nexilin, and F-actin (Dang et al, 2018;Wang et al, 2020). These results are consistent with our GSEA analysis results.…”
Section: Discussionsupporting
confidence: 93%
“…There are reports that BAP31 promotes proliferation and metastasis in multiple cancers (Dang et al, 2018;Wang et al, 2019Wang et al, , 2020Xu et al, 2019). In the current study, we have initially illustrated that BAP31 promoted HCC migration, invasion and metastasis both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 58%
“…There are reports that BAP31 knockdown reduces expression level of TGF-β1, MMP-2, MMP-9, ROCK1, α-SMA, Vimentin and N-cadherin in cervical cancer (Wang et al, 2019), and BAP31 affects F-actin distribution to promote migration and invasion of lung cancer cells (Wang et al, 2020). Recent study also suggests that miR-362 can inhibit tumor progression via SNAIL1) and E-cadherin (CDH1) mRNA expression in Li-7 and Huh7 cell, which were divided into four groups: vector, BAP31 (DMSO-control), BAP31 (MK2206 2.5 µM) and BAP31 (MK2206 5 µM).…”
Section: Discussionmentioning
confidence: 99%
“…KRT8 was used for cancer prognosis, including for ADC patients [ 192 , 193 ], whereas KRT10 was found to be a useful biomarker for the treatment response in lung cancer [ 194 ]. Keratins appeared to be subjected to post-translational modifications when they were expressed in tumors [ 195 , 196 ].…”
Section: Discussionmentioning
confidence: 99%